Short I⋯O Interactions in the Crystal Structures of Two 2-Iodo-Phenyl Methyl-Amides as Substrates for Radical Translocation Reactions - Ahtsham Ishaq; John M. D. Storey; William T. A. Harrison (Chemistry, 2023)
Radical translocation reactions are finding various uses in organic synthesis, in particular the stereospecific formation of complex natural products. In this work, the syntheses and single-crystal structures of two substituted 2-iodo-phenyl methyl-amides are reported, namely cyclo-propane carboxylic acid (2-iodo-phenyl)-methyl-amide, C11H12INO (1), and cyclo-heptane carboxylic acid (2-iodo-phenyl)-methyl-amide, C15H20INO (2). In each case, the methyl-amide group has a syn conformation, and this grouping is perpendicular to the plane of the benzene ring: these solid-state conformations appear to be well setup to allow an intramolecular hydrogen atom transfer to take place as part of a radical translocation reaction. Short intermolecular I⋯O halogen bonds occur in each crystal structure, leading to [010] chains in 1 [I⋯O = 3.012 (2) Å] and isolated dimers in 2 [I⋯O = 3.024 (4) and 3.057 (4) Å]. The intermolecular interactions are further quantified by Hirshfeld surface analyses.